The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/2014pa002653
|View full text |Cite
|
Sign up to set email alerts
|

Middle Miocene climate instability associated with high‐amplitude CO2 variability

Abstract: The amplitude of climatic change, as recorded in the benthic oxygen isotope record, has varied throughout geological time. During the late Pleistocene, changes in the atmospheric concentration of carbon dioxide (CO 2 ) are an important control on this amplitude of variability. The contribution of CO 2 to climate variability during the pre-Quaternary however is unknown. Here we present a new boron isotope-based CO 2 record for the transition into the middle Miocene Climatic Optimum (MCO) between 15.5 and 17 Myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
142
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(163 citation statements)
references
References 54 publications
(108 reference statements)
21
142
0
Order By: Relevance
“…Although somewhat arbitrary, these values are within the range of published estimates. The 400 ppmv MMCO estimate represents a maximum rather than a mean (within the interval ~15-17 Ma) and is in favourable agreement with Foster et al (2012) and Tripati et al (2009), as well as with the most recent alkenone-and boron isotope-based p CO 2 reconstructions for the MMCO by Zhang et al (2013) and Greenop et al (2014). The 200 ppmv MMG estimate represents a minimum rather than a mean (within the interval ~12-15 Ma) and is in good agreement with Foster et al (2012) andPagani et al (2005).…”
Section: Atmospheric Co2 Concentrationsupporting
confidence: 87%
“…Although somewhat arbitrary, these values are within the range of published estimates. The 400 ppmv MMCO estimate represents a maximum rather than a mean (within the interval ~15-17 Ma) and is in favourable agreement with Foster et al (2012) and Tripati et al (2009), as well as with the most recent alkenone-and boron isotope-based p CO 2 reconstructions for the MMCO by Zhang et al (2013) and Greenop et al (2014). The 200 ppmv MMG estimate represents a minimum rather than a mean (within the interval ~12-15 Ma) and is in good agreement with Foster et al (2012) andPagani et al (2005).…”
Section: Atmospheric Co2 Concentrationsupporting
confidence: 87%
“…5 we show the new reference CO 2 results together with proxy data over three periods for which data are relatively abundant: the Late (Pagani et al, 1999(Pagani et al, , 2011Badger et al, 2013) are indicated by orange asterisks. Boron-isotope-based data (Pearson et al, 2009;Foster et al, 2012;Greenop et al, 2014;Martínez-Botí et al, 2015) are indicated by blue plus symbols. Stomata-based data (Van der Burgh et al, 1993;Kürschner, 1996;Kürschner et al, 2008;Retallack, 2009) Pliocene (3.5 to 2.5 Myr ago), the Middle Miocene (18 to 13 Myr ago), and the Early Oligocene (35 to 30 Myr ago).…”
Section: Comparison To Proxy Co 2 Datamentioning
confidence: 99%
“…Stomata-based data (Van der Burgh et al, 1993;Kürschner, 1996;Kürschner et al, 2008;Retallack, 2009) Pliocene (3.5 to 2.5 Myr ago), the Middle Miocene (18 to 13 Myr ago), and the Early Oligocene (35 to 30 Myr ago). The data are based on three important proxies (see also Beerling and Royer, 2011): alkenones (Pagani et al, 1999(Pagani et al, , 2011Badger et al, 2013), boron isotopes (Pearson et al, 2009;Foster et al, 2012;Greenop et al, 2014;Martínez-Botí et al, 2015), and stomata (Van der Burgh et al, 1993;Kürschner, 1996;Kürschner et al, 2008;Retallack, 2009). During the Late Pliocene, the simulated CO 2 is more variable than the alkenone data from Badger et al (2013) (Fig.…”
Section: Comparison To Proxy Co 2 Datamentioning
confidence: 99%
“…Boron isotope measurements on fossil carbonates thus have the potential to constrain changes in pH and CO 2 over geological time (Pearson and Palmer 2000;Hönisch et al 2009;Rae et al 2014;Penman et al 2014;Greenop et al 2014;Martínez-Botí et al 2015a). The shells, or "tests", of foraminifera, which are single-celled protists, provide a convenient host for the d 11 B-pH proxy, being widely distributed throughout the world's oceans, relatively well-preserved in marine sediment cores, and having chemistry that closely reflects surrounding seawater conditions (Wefer et al 1999;Erez 2003).…”
Section: Introductionmentioning
confidence: 99%